2015
DOI: 10.1097/scs.0000000000001549
|View full text |Cite|
|
Sign up to set email alerts
|

The Relationship Between Facial Asymmetry and Nasal Septal Deviation

Abstract: We demonstrate that there is a strong relationship between nasal septal deviation to the right and a wider right hemiface in facial asymmetry patients. Also, facial asymmetry patients tend to have a wider right side of the face compared to the left side.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 13 publications
(15 reference statements)
1
13
0
Order By: Relevance
“…Previous studies comprising adolescents and adult subjects (14–71 years old) revealed an association between nasal septum deviation and deviated nose with facial asymmetries through photographic analysis (Hafezi et al, 2010; Kim et al, 2011) and using computed tomography (CT) (Hartman et al, 2016; Holton et al, 2012; Hun et al, 2015). Hafezi et al (2010) found a high incidence of facial asymmetry in patients with deviated nose.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies comprising adolescents and adult subjects (14–71 years old) revealed an association between nasal septum deviation and deviated nose with facial asymmetries through photographic analysis (Hafezi et al, 2010; Kim et al, 2011) and using computed tomography (CT) (Hartman et al, 2016; Holton et al, 2012; Hun et al, 2015). Hafezi et al (2010) found a high incidence of facial asymmetry in patients with deviated nose.…”
Section: Introductionmentioning
confidence: 99%
“…Hafezi et al (2010) found a high incidence of facial asymmetry in patients with deviated nose. The direction of septal deviation was associated with growth differences between the right and left sides of the face (Kim et al, 2011), as well as it was shown that there was a strong relationship between NSD to the right and wider right hemiface in patients with facial asymmetry (Hun et al, 2015). The results of the study by Holton et al (2012) indicated a significant correlation between nasal septum volume and craniofacial shape, probably due to the need to accommodate the septal volume.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Facial asymmetry (FA) is a common complaint of patients undergoing orthognathic surgery [1]. Although the severity of FA is mainly influenced by hard tissue asymmetry of the mandible and maxilla [2], soft tissue asymmetry, such as lip canting or philtrum deviation, is also an important factor that can cause an unbalanced facial appearance [3, 4].…”
Section: Introductionmentioning
confidence: 99%